Locational analysis of public health facilities: a case study of Telok Panglima Garang, Selangor, Malaysia - S.S, Radiah Shariff; Omar, Mohd; Moin, Noor Hasnah; Smith, David K. (Malaysian Journal of Science, 2010)
As the economy and standard of living have improved, the demand has increased from the public for a better healthcare system. In developing countries like Malaysia, planning of public healthcare facilities is one of the keys for achieving an acceptable level of health. This is especially the case in rural areas. Location-allocation models can play a significant role in ensuring that facilities are accessible to the population. This study focuses on a selected area, Telok Panglima Garang, Selangor which is currently served by 5 public health facilities. The health delivery system in this area is analyzed in order to develop qualitative insights into the problem of ensuring that the local population has access to good healthcare. We identify variables like population coverage and average traveled distance by patients that influence the quality of the services. The existing public health delivery system is analyzed using both the Maximal Covering Location Problem (MCLP) and the p-median method. The limitations of the study and directions for future research are presented at the end of the paper.